Amphetamine and Clonidine Toxicity Resulting in Posterior Reversible Encephalopathy Syndrome. Issue 12 (10th December 2021) - Minhaj, Faisal Syed; Schult, Rachel F.; Dvorak, Peter; Nacca, Nicholas
Abstract: Amphetamine toxicity typically presents with hypertension and tachycardia. Conversely, clonidine acts as an agonist at central α2 and imidazoline receptors, which may cause brief initial hypertension followed by hypotension and bradycardia in overdose. We report a case of mixed ingestion resulting in posterior reversible encephalopathy syndrome (PRES) successfully treated with phentolamine. A 17-year-old male adolescent presented to the emergency department 2 hours after ingesting up to 25 each of clonidine 0.1-mg tablets and dextroamphetamine 10 mg extended-release capsules. He reported nausea and fatigue with initial blood pressure (BP) 145/95 mm Hg and heart rate (HR) 52 beats per minute (bpm). Nine hours postingestion (HPI), the patient developed headache, photophobia, and confusion with BP 182/111 mm Hg and HR 48 bpm. A computed tomography scan of the head revealed generalized fullness of the cerebellum, upward bulging of the tentorial leaflets, effacement of the fourth ventricle, and crowding of the foramen magnum, suspicious for an atypical presentation of PRES. The patient's systolic BP rose over 200 mm Hg and treated with 2 mg of intravenous phentolamine at 14 HPI. Blood pressure decreased to 133/82 mm Hg, and HR increased to 56 bpm with improvements in headache. Following repeat doses of phentolamine, nicardipine was initiated and increased to 2.5 mg/h for 12 hours. The patient was stable with normal vital signs at 36 HPI. The delayed presentation of hypertensive emergency with PRES may have been due to the actions of extended-release dextroamphetamine and the α2-agonistic effects of clonidine. Phentolamine was chosen for its α1-antagonism and was effective in managing symptoms.